ARTIFICIAL INTELLIGENCE, DEFINITIONS AND APPLICATIONS: the use of intelligent systems for the benefit of medicine - Santos, Andressa Maxwara Jovino dos; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
Artificial Intelligence is a reality in different areas of science, whether applied to the mobile device that is easily accessible to people, or in autonomous systems capable of using the entire tools or performing complex operations. This study described how to better understand what the concept of Artificial Intelligence is, rescue, including the Turing test, which allows us to assess whether a machine is capable of being aware of making decisions, affecting a human brain. In view of the different applications of Artificial Intelligence, the study, followed, if a specific area, which is a drug, in order to show some examples in intelligent systems already makes a difference in the list of diseases, diagnostic performances, surgical procedures and procedures . Who realizes, from this study, that Artificial Intelligence has a huge potential to change the way each procedure is performed, or that it can be valuable for an evolution of the different areas that can support these technologies, including, for certain, medicine.